Testing the causes of richness patterns in the paleotropics: time and diversification in cycads (Cycadaceae) - Liu, Jian; Lindstrom, Anders; Nagalingum, Nathalie; Wiens, John; Gong, Xun (Dryad, 2021)
The paleotropics harbor many biodiversity hotspots and show many different
species richness patterns. However, it remains unclear which factors are
the most important in directly shaping richness patterns among regions in
the paleotropics (i.e. diversification rates, colonization times,
dispersal frequency). Here we used Cycadaceae as a model system to test
the causes of regional richness patterns in the paleotropics. Specifically
we tested the roles of dispersal frequency, colonization time,
diversification rates, and their combined role in explaining richness
patterns among regions. We generated a well-sampled, time-calibrated
phylogeny and then used this to estimate dispersal events, colonization
times, and diversification rates. Richness patterns were significantly
associated with the timing of the first colonization of each region, and
were best explained by the combined effects of colonization time and
diversification rates. The number of dispersal events into each region and
the diversification rates of species in each region were not significantly
related to richness. Ancestral-area reconstructions showed frequent
migrations across Wallace’s Line, with a higher diversification rate east
of Wallace’s Line than west of it. Overall, our study shows that
colonization time can be an important factor for explaining regional
richness patterns in the paleotropics.
The readme file contains an explanation of each file used in this work.
Information on how the analyses were done can be found in the associated
manuscript referenced above.